Pengaruh Olahraga Tradisional Lari Balok terhadap Kemampuan Motorik Anak SDN Wangun - Latif, Moch; Bakhri, Rafdlal Saeful; Faiz Faozi; Hidayatulloh, Dede Taufik; Ismail, Nasrul (SPRINTER: Jurnal Ilmu Olahraga, 2024)
This research aims to examine the influence of the traditional sport of beam running on children's motor skills at SDN Wangun students. Children's motor skills are an important aspect of physical development which includes coordination skills, balance, speed, agility and strength. The traditional sport of block running, which involves running on blocks, is believed to provide significant benefits for children's motor development. The research method used was experimental with the design used in this research being One Group Pretest- posttest, namely experimental research carried out on only one group that was chosen at random and no tests were carried out for the stability and clarity of the group's condition before being given treatment. This treatment was given to the experimental group, namely the Extracurricular Traditional Sports Beam Running at SDN Wangun, which consisted of 15 students. This treatment was given over 12 meetings, where every week there were 3 meetings with details of 1 pretest, 10 treatments and 1 posttest. The results showed that there was a significant increase in the motor skills of students who participated in beam running. This improvement was seen in all aspects tested, especially in balance and coordination. Statistical analysis using the t test showed a significant difference (p< 0.05) between the pre-test and post-test results of the experimental group.